Home Blood Pressure Control and Drug Prescription Patterns among Thai Hypertensives: A 1-Year Analysis of Telehealth Assisted Instrument in Home Blood Pressure Monitoring Nationwide Pilot Project. (14th April 2021) - Sakulsupsiri, Anut; Chattranukulchai, Pairoj; Siwamogsatham, Sarawut; Boonchayaanant, Patchaya; Naeowong, Witthawat; Ariyachaipanich, Aekarach; Lertsuwunseri, Vorarit; Rungpradubvong, Voravut; Satitthummanid, Sudarat; Puwanant, Sarinya; Srimahachota, Suphot; Buddhari, Wacin; et al.
Abstract : Background . Several interventions have been proposed to improve hypertension control with various outcomes. The home blood pressure (HBP) measurement is widely accepted for assessing the response to medications. However, the enhancement of blood pressure (BP) control with HBP telemonitoring technology has yet to be studied in Thailand. Objective . To evaluate the attainment of HBP control and drug prescription patterns in Thai hypertensives at one year after initiating the TeleHealth Assisted Instrument in Home Blood Pressure Monitoring (THAI HBPM) nationwide pilot project. Methods . A multicenter, prospective study enrolled treated hypertensive adults without prior regular HBPM to obtain monthly self-measured HBP using the same validated, oscillometric telemonitoring devices. The HBP reading was transferred to the clinic via a cloud-based system, so the physicians can adjust the medications at each follow-up visit on a real-life basis. Controlled HBP is defined as having HBP data at one year of follow-up within the defined target range (<135/85 mmHg). Results . A total of 1, 177 patients (mean age 58 ± 12.3 years, 59.4% women, 13.1% with diabetes) from 46 hospitals (81.5% primary care centers) were enrolled in the study. The mean clinic BP was 143.9 ± 18.1/84.3 ± 11.9 mmHg while the mean HBP was 134.4 ± 15.3/80.1 ± 9.4 mmHg with 609 (51.8%) patients having HBP reading <135/85 mmHg at enrollment. At one year of follow-up after implementing the HBP telemonitoring, 671 patients (57.0%) achieved HBP control. Patients with uncontrolled HBP had a higher prevalence of dyslipidemia and greater waist circumference than the controlled group. The majority of uncontrolled patients were still prescribed only one (36.0%) or two drugs (34.4%) at the end of the study. The antihypertensive drugs were not uptitrated in 136 (24%) patients with uncontrolled HBP at baseline. Calcium channel blocker was the most prescribed drug class (63.0%) followed by angiotensin-converting enzyme inhibitor (44.8%) while the thiazide-type diuretic was used in 18.9% of patients with controlled HBP and 16.4% in uncontrolled patients. Conclusion . With the implementation of HBP telemonitoring, the BP control rate based on HBP analysis was still low. This is possibly attributed to the therapeutic inertia of healthcare physicians. Calcium channel blocker was the most frequently used agent while the diuretic was underutilized. The long-term clinical benefit of overcoming therapeutic inertia alongside HBP telemonitoring needs to be validated in a future study.